The Influence of Leadership Style on the Effectiveness of Office Management in Integrated Services Business Offices - Hsing-lee, Wu (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
The aim of this analysis was to ascertain the degree to which the Head of the Integrated Business Services Office's Leadership Style affects the efficacy of the Integrated Business Services Office's management. In data analysis, a descriptive study of one variable was performed to determine the percentage trend of each test variable; second, the commodity moment correlation formula was used to analyze variable relationships; and third, a basic equation model was used to analyze the impact relationship between the independent and dependent variables. The data for this study were processed using a micro statistical program with the assistance of a computer program. The data analysis and interpretation of the study's hypotheses indicate that there is a significant relationship and influence between the variable leadership style of the Integrated Business Services Office's Head and the effectiveness of the Integrated Business Services Office's management, at the 5% significance level or P = 0, 05, respectively.